2016
DOI: 10.1111/codi.13305
|View full text |Cite
|
Sign up to set email alerts
|

No benefit of extended mesenteric resection with central vascular ligation in right‐sided colon cancer

Abstract: The study showed no survival benefit by more extended mesenteric resection, indicating that there is no need to extend the mesenteric resection to involve the MCVs in cancer of the caecum or ascending colon. On the contrary, increased peri-operative mortality by more extensive mesenteric resection was noted suggesting that a more conservative approach may be favourable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 25 publications
1
31
0
1
Order By: Relevance
“…Thus, we have not made any attempt to evaluate CME‐surgery and have not stated any such aim. On the contrary we clearly state in the second to last paragraph of the Discussion that: ‘the present study does not evaluate the full CME concept but only the impact of extended mesenteric resection including adjacent vascular branches’ .…”
mentioning
confidence: 67%
“…Thus, we have not made any attempt to evaluate CME‐surgery and have not stated any such aim. On the contrary we clearly state in the second to last paragraph of the Discussion that: ‘the present study does not evaluate the full CME concept but only the impact of extended mesenteric resection including adjacent vascular branches’ .…”
mentioning
confidence: 67%
“…Several studies have shown an improved prognosis in colon cancer after CME . However, there has been concern that the more extensive dissection close to retroperitoneal organs and large blood vessels may be hazardous and cause an increased morbidity and mortality .…”
Section: Discussionmentioning
confidence: 99%
“…However, the observational design of these studies does not provide robust evidence that the improvements rely mainly on CME surgery. In contrast, CME surgery has been suggested to increase the risk of severe adverse intra‐operative events, due to exposure of vital retroperitoneal organs such as the duodenum, pancreas and mesenteric root .…”
Section: Introductionmentioning
confidence: 99%
“…In the study of Gao et al, the CME resected specimen presented a higher number of resected lymph nodes (24 vs. 20, P=0.002), and all the morphometric data of the resected specimen, such as area of the mesentery (right colon: 13,052 vs. 9,093 mm 2 ; sigmoid colon: 10,317 vs. 7475 mm 2 ) and tumor to high tie distance (right colon: 129 vs. 113 cm; sigmoid colon: 143 vs. 121 cm), favoring CME (1) (see Table 2). Olofsson et al investigated the clinical data for ceacum and ascending colon tumors, from Swedish Colorectal Cancer Registry, related to oncological impact of central ligation of (I) ileocolic +/− right colic vessels (390 patients); (II) ileocolic and right branch of the middle colic (1,360 patients); and (III) ileocolic and middle colic vessels (334 patients) (22). There were no differences regarding 3-year OS, 3-year DFS, and local recurrence rate, with an increase of perioperative mortality from 0.8% to 3.6% with extended resections (P=0.025) (22).…”
Section: Quality Of the Resected Specimenmentioning
confidence: 99%